Generation of donor-specific immunotolerance in renal-allograft recipients - V. A. Goryainov; M. M. Kaabak; M. M. Morozova; L. A. Shishlo; N. N. Babenko; A. K. Zokoyev (Трансплантология (Москва))
The kidney cannot be successfully grafted without immunosuppressive therapy. A unicenter retrospective study has evaluated the efficiency of immunosuppression with daclizumab (Zenapax) versus alemtuzumab (Campath).Subjects and methods. After renal allotransplantation, 64 patients, including 34 and 30 patients, were treated with daclizumab and alemtuzumab, respectively. The absolute count of peripheral blood lymphocytes was measured. Renal grafts were morphologically assessed as described by Banff.Results. After administration of alemtuzumab, there was a more pronounced decrease in the absolute count of peripheral blood lymphocytes and the rate of acute rejection crisis was 1.5 times lower than that after use of daclizumab.Conclusion. During the study, alemtuzumab demonstrated a more marked immunosuppressive activity than did daclizumab and the ability of the former to generate donor-specific immunotolerance in renal-allograft recipients.